Gentiopicroside improves high-fat diet-induced NAFLD in association with modulation of host serum metabolome and gut microbiome in mice - Wang, Lijuan; Jiang, Yuxin; Yu, Qian; Xiao, Chunping; Sun, Jin; Weng, Lili; Qiu, Ye (Frontiers in Microbiology, 2023)
The incidence of non-alcoholic fatty liver disease is increasing every year, and there is growing evidence that metabolites and intestinal bacteria play a causal role in NAFLD. Gentiopicroside, a major iridoids compound in gentian, has been reported to reduce hepatic lipid accumulation. However to date, no studies have confirmed whether the predominance of gentiopicroside is related to metabolites and intestinal bacteria. Therefore, we sought to study whether the hypolipidemic effect of Gentiopicroside is related to metabolic function and intestinal flora regulation. In the present study, C57BL/6J mice were fed a high-fat diet for 12 weeks, followed by a high-fat diet with or without gentiopicroside for 8 weeks, respectively. The Gentiopicroside intervention reduced body weight gain, liver index, and decreased serum biochemical parameters such as alanine aminotransferase, aspartate aminotransferase, and triglycerides in high-fat fed mice. The effect of Gentiopicroside on non-alcoholic fatty liver disease was studied using serum untargeted metabolomics and 16S rDNA assay. Metabolomic analysis showed that the addition of Gentiopicroside significantly altered the levels of amino acids, unmetabolized Gentiopicroside after administration, and metabolites such as Cinnoline, Galabiosylceramide, and Tryptophyl-Tyrosine, which are involved in the pathways regulating bile secretion, tryptophan metabolism, and lipid metabolism. Analysis of intestinal bacteria showed that gentiopicrosides altered the community composition structure of intestinal bacteria, characterized by an increase and a decrease in beneficial and harmful bacteria, respectively. In addition, correlation analysis showed that the effect of Gentiopicroside on metabolites was positively correlated with intestinal flora Bacteroides, Lactobacillus, Muribaculum, and Prevotellaceae_UCG_001. Finally, the combined analysis revealed that metabolites were associated with the regulation of Firmicutes and Actinobacteria and positively correlated with lipid levels. These results suggest that Gentiopicroside may be a potential agent for the prevention of intestinal disorders and the alleviation of non-alcoholic fatty liver disease.